The Students’ Characters Analysis in Physics Learning Process - Anita Anita; Fety Novianty (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
The character affects a person’s quality of life. Having a good character is expected to have the ability to improve his/her quality of life. This study aims to describe the characters of students, namely responsibility, curiosity/creativity, honesty, tolerance, perseverance, and discipline. This descriptive research utilizes indirect communication techniques in collecting data. The data collection tools used are in the form of character questionnaires. The student character questioners are developed based on validated character indicators with a value of 81% with decent character. Based on the results of the analysis of the character questionnaires data that was filled out by the students, it was found that the characters of responsibility, creativity, honesty, perseverance, and discipline were classified began to develop, and the character of tolerance was classified as seen. However, in general, the character of students is classified as began to develop.